Ranking and Validation of Constructs in the International Strategic Marketing Model of the Cement Industry - Momeni, Mohammad Hosein; Rousta, Alireza; Ahmadi Sharif, Mahmoud (Business, Marketing, and Finance Open, 2024)
The cement industry is a strategic sector that plays a crucial role in economic and infrastructural development and holds the largest share of production among other industries. In today’s world, cement, as a future-oriented and strategic commodity, is regarded as a prerequisite for development, employment, and progress in all countries. This study aims to propose an international strategic marketing model for the cement industry during the sanctions period. The research is quantitative, and the statistical population includes managers and experts in the cement industries of Tehran province. The software tools used for data analysis are SPSS26 and SmartPLS3. The researcher seeks to answer the following questions: What are the validations of the constructs in the international strategic marketing model of the cement industry during the sanctions period? How are the constructs of the international strategic marketing model of the cement industry during the sanctions period ranked? How do the constructs of the international strategic marketing model of the cement industry during the sanctions period relate to each other?